ANALISIS SENSITIVITAS PUMP RATE DAN FRACTURE HEIGHT DALAM PREDIKSI DESAIN OPTIMAL GEOMETRI REKAHAN SEDERHANA PADA RESERVOIR SHALE GAS - W Lumbanraja, Nicolas
Hydraulic fracturing is a stimulation technique used to increase effective radius of well by pumping pressurized fracturing fluid injected through well to formation in order to break it. Fracturing conductivity is designed higher than formation conductivity with sufficient length so that fluid capacity in reservoir and production increase. This technology is fit to extract fluid from unconventional reservoir such as shale gas reservoir. There are several “major” fracture variables in designing geometry model of hydraulic fracturing in shale gas, these include: height, modulus, fluid loss, apparent fracture toughness, fluid viscosity and pump rate. This thesis focuses on discuss about pump rate and fracture height. This modeling will be focused on making simple fracture geometry on Barnett shale, Marcellus shale, and Woodford shale. After that, there will be pump rate and fracture sensitivity analysis applied to all these reservoirs to obtain optimal hydraulic fracturing geometry model based on efective conductivity and fracturing fluid efficiency. The best effective conductivity in Barnett shale achieved by using 300 bbl/min pump rate, while Marcellus and Woodford achieved by using 150 bbl/min pump rate. The best fluid efficiency achieved by using 450 bbl/min pump rate. Based on fracture height sensitity analysis, with constraint maximum hydraulic fracture length 700 ft and maximum proppant concentration 8 PPA, the highest fluid efficiency achieved by fracture height around 20% from the thickness of formation.